Environmentally friendly Fe3+-activated near-infrared-emitting phosphors for spectroscopic analysis - Jing Wang (Light: Science & Applications, 2022)
Abstract Highly efficient Fe3+-activated Sr2-y Ca y (InSb)1-z Sn2z O6 broadband near-infrared-emitting phosphors with tunable emission from 885 to 1005 nm are developed as alternative for primarily studed toxic Cr3+-activated near-infrared-emitting phosphors for application in spectroscopy analysis.